Current Trend in the Cancer Symptoms - Noel Samuel Macwan (Current Progress in Medicine and Medical Research Vol. 9, 2023)
This Chapter mainly focuses on Cancer related symptoms in the diagnosed case and non specific symptoms of cancer and also in the non curable cancer Patient. It also shows the presence of such symptoms in the pre and post Chemotherapy, Radiation therapy and in Surgical Intervention for the patients undergoing Cancer Treatment. Cancer being the 2nd leading cause of mortality in the world is a major public concern can affect any part of the body. Breast cancer in the females and prostrate cancer in the males are most commonly occurring form of the Cancer. As it is diagnosed late in the developing countries higher rates of its occurrence are found. Cancer related symptoms like Anxiety, depression, psychological disorders, sleep disorder, fatigue, pain and functional impairment. Cancer patients suffer from high burden of these symptoms which could occur as complications, initially after therapy or during long term therapy may last from months to years. This leads to feeling of helplessness and hopelessness which can seriously affect the quality of life.